The Role of Deubiquitinating Enzymes in Synaptic Function and Nervous System Diseases - Jennifer R. Kowalski; Peter Juo (Neural Plasticity)
Posttranslational modification of proteins by ubiquitin has emerged as a critical regulator of synapse development and function. Ubiquitination is a reversible modification mediated by the concerted action of a large number of specific ubiquitin ligases and ubiquitin proteases, called deubiquitinating enzymes (DUBs). The balance of activity of these enzymes determines the localization, function, and stability of target proteins. While some DUBs counter the action of specific ubiquitin ligases by removing ubiquitin and editing ubiquitin chains, other DUBs function more generally to maintain the cellular pool of free ubiquitin monomers. The importance of DUB function at the synapse is underscored by the association of specific mutations in DUB genes with several neurological disorders. Over the last decade, although much research has led to the identification and characterization of many ubiquitin ligases at the synapse, our knowledge of the relevant DUBs that act at the synapse has lagged. This review is focused on highlighting our current understanding of DUBs that regulate synaptic function and the diseases that result from dysfunction of these DUBs.